Kepemimpinan Perempuan di Kelurahan Tanjungpura Kabupaten Karawang: Studi Kasus di Kelurahan Tanjungpura, Kabupaten Karawang - Shabihah Putri Az-Zahra; Rachmat Ramdani; Rahman (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study analyzes the implementation of female leadership within the local government bureaucracy of Kelurahan Tanjungpura, Karawang Regency, a setting historically dominated by male leaders. Utilizing a qualitative case study approach, this research provides an in-depth exploration of the leadership style of the first female Lurah (sub-district head) in the area. The analysis is framed by Bass and Avolio's (1994) theory of transformational leadership, examining its four core dimensions: Idealized Influence, Inspirational Motivation, Intellectual Stimulation, and Individualized Consideration. Data were collected through in-depth interviews with the Lurah, her staff, and community members, supplemented by direct observation and documentation. The findings indicate that the Lurah effectively employs all four dimensions of transformational leadership. She establishes herself as a credible role model (Idealized Influence), inspires collective action through a shared vision and direct participation (Inspirational Motivation), fosters a collaborative environment for innovation (Intellectual Stimulation), and builds a loyal, resilient team through personal mentorship (Individualized Consideration). The study concludes that the transformational leadership style is a highly effective strategy for female leaders to build legitimacy, navigate socio-cultural challenges, and enhance community participation in local governance.